Pleuropulmonary complications of pancreatitis. Issue 3 (May 1968) - Kaye, Michael D.
Abstract : Pancreatitis, in common with many other upper abdominal diseases, often leads to pleuropulmonary complications. Radiological evidence of pleuropulmonary abnormality was found in 55% of 58 cases examined retrospectively. The majority of such abnormalities are not specific for pancreatitis; but a particular category of pleural effusions, rich in pancreatic enzymes, is a notable exception. A patient with this type of effusion, complicated by a spontaneous bronchopleural fistula and then by an empyema, is reported. The literature relating to pancreatic enzyme-rich pleural effusions (pathognomonic of pancreatitis) is reviewed. Of several possible mechanisms involved in pathogenesis, transdiaphragmatic lymphatic transfer of pancreatic enzymes, intrapleural rupture of mediastinal extensions of pseudocysts, and diaphragmatic perforation are the most important. The measurement of pleural fluid amylase, at present little employed in this country, has considerable diagnostic value. Enzyme-rich effusions are more commonly left-sided, are often blood-stained, are frequently associated with pancreatic pseudocysts, and—if long standing—may be complicated by a bronchopleural fistula.